‟VERTIGO”, FANTASME MASCULIN, MASQUE FEMININ - Muriel MOSCONI (Studia Universitatis Babeș-Bolyai. Philosophia, 2020)
Vertigo, Masculine Phantasy, Feminine Mask. Vertigo allows us to shed light on how an obsessive symptom is articulated with a typical masculine phantasy and how it unravels itself during the crossing of this phantasy. On the feminine side, it teaches us in what respect can it be onerous to wear the mask of the object of the masculine phantasy.